NILAI-NILAI PENDIDIKAN AKHLAK DALAM FILM KELUARGA CEMARA - Yustika Yustika (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
This study aims to reveal about: 1) The values of moral education in cemara family films. 2) The review of the values of cemara family film education. This research reveals the cauldron approach and type of research is library research. Data collection using observation and documentation. After the data is collected, data analysis techniques are held by conducting content analysis. Then after processing then continued with the technique of checking the validity of the data obtained by doing perseverance observation and extension of observation. The results showed that: 1. The values of moral education in the family film cemara namely Akhlak against Allah Swt: Bertakwa, Ikhlas, Syukur. Morality towards yourself: Patient, Tawadhu, Forgiving. Morality towards the family: Respect for both parents, Parental affection for their child. Morality towards the environment: Nurture the environment and Love the environment. 2. The relevensi of moral education values in family films fir with education that is equally inviting to do good and avoiding the deplorable nature in accordance with the norms that have been set both to God, himself, to others, namely family and society.